When Did the Swahili Become Maritime?. Issue 1 (25th January 2015) - Fleisher, Jeffrey; Lane, Paul; LaViolette, Adria; Horton, Mark; Pollard, Edward; Quintana Morales, Eréndira; Vernet, Thomas; Christie, Annalisa; Wynne‐Jones, Stephanie
ABSTRACT In this article, we examine an assumption about the historic Swahili of the eastern African coast: that they were a maritime society from their beginnings in the first millennium C.E. Based on historical and archaeological data, we suggest that, despite their proximity to and use of the sea, the level of maritimity of Swahili society increased greatly over time and was only fully realized in the early second millennium C.E. Drawing on recent theorizing from other areas of the world about maritimity as well as research on the Swahili, we discuss three arenas that distinguish first‐ and second‐millennium coastal society in terms of their maritime orientation. These are variability and discontinuity in settlement location and permanence; evidence of increased engagement with the sea through fishing and sailing technology; and specialized architectural developments involving port facilities, mosques, and houses. The implications of this study are that we must move beyond coastal location in determining maritimity; consider how the sea and its products were part of social life; and assess whether the marine environment actively influences and is influenced by broader patterns of sociocultural organization, practice, and belief within Swahili and other societies. [maritime, fishing and sailing, long‐distance trade, Swahili, eastern Africa]